FAKTOR – FAKTOR YANG MEMPENGARUHI INITIAL RETURN PADA INITIAL PUBLIC OFFERING (IPO) - Tiara Morina; Rida Rahim (Menara Ilmu, 2020)
This study was conducted to determine the factors that influence the initial return on the initial public offering of non-financial companies for the period of 2016 to 2018. The variables in this research are return on assets, debt to equity ratio, earnings per share, company size, appointed underwriter, and auditor reputation, and initial returns. The sampling technique is purposive sampling and we get 86 companies. The data analysis technique is multiple regression, where the results obtained are return of assets and auditor’s reputation is insignificant and positive of initial returns, debt to equity ratio and company size is insignificant and negative. Earnings per share variable and the influence of underwriters have a significant and positive effect. Keywords: initial return, return on assets, debt to capital ratio, earnings per share, company size, reputation underwriter, and auditor's reputation